Study of Biochemical Polymorphisms for the Purpose of Germ Plasm Resources Conservation of Native Livestock in Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: Local breeds have an irreplaceable characteristic, such as full adaptation to local enviromnental, parasitical, and sanitary situation but their weakness is the usual low performance. Today, as a progress in artificial insemination and selection for economically in1portant traits, genetic variation between breeds is w1doubtedly decreasing. There are some difficulties to identify autochtonous populations and to measure the degree of genetic erosion. For the purpose to evaluate the genetic constitution and genetic diversity of indigenous breeds, an electrophoresis protein techniques is one of the rcsearch progranune deals. The investigations being carried out are biochemical genetics of cOmmercial oysters, as an exemple. The study have been initiated to evaluate the genetic variability and thc genetic relationships of the native populations of oysters, Crassostrea virginica, from the Mcxican coast of the Gulf of Mexico. The prcsence of the diagnostic allele MDH 1-94 suggest a possiblc introgression of C. rhizophorae character into somc C. virginica populations Key Words: Electrophoresis, Gcnetic Variability, Polymorphisms, Nativc Livestock (Oysters)